ANALISIS ISI FOTO BERITA PADA RUBRIK “JEPRET” DI HARIAN POS METRO MEDAN - Novri Maulana, Taufik Walhidayat (Universitas Medan Area, 2013)
The research aims is to observe content of photo news on ?Jepret? rubric of Pos Metro daily. A photo has the ability to present a news in detail. Reader does not explanation such narrative description. Therefore, a photo able to record anything and objectively present the event that contain element of news. This research use content analysis to observe and measure the content of communication medium. The result shows that the appearance and size of ?Jepret? rubric on the daily accordingly to Pos Metro policy,